The Feral at Home: The Rogue Trajectory and Unexpected Relations of a “Feral Pig” - Keil, Paul (Humanimalia, 2025)
A feral pig in Australia is an introduced pig who lives beyond the constraints of human husbandry or expresses wild physiological traits. These animals are typically characterized as alien, overwhelmingly destructive, and toxic. The only acceptable relation is to kill them. I met Pig-pig during a series of interviews — she was a wild-caught pig living on the property of Scott, a pig hunter. Primarily drawn from conversations with Scott, this paper is an account of Pig-pig that explores a feral pig trajectory that partially existed outside of dominant discourses and practices. Writing about Pig-pig and Scott helps expand our understanding of feral pigs (and hunters) — including who they are and who they can be with. It also requires being attuned to a more-than-human agency that exceeds apprehension and determination, to a degree. First, I analyse how this individual animal eludes common categories and ways of enacting feral pigs. Next, I explore the unexpected and compelling relations she developed and consider how her place in an unauthorized multispecies home enabled her to become Pig-pig. Finally, I ask how Pig-pig was still alive and what it reveals about the limits of Scott’s power and the obligations he had towards other claims on Pig-pig, by human and nonhuman alike. The paper concludes with Pig-pig being killed, demonstrating the limits of alternate trajectories of pig becoming in a world geared towards their death.